2018
DOI: 10.1155/2018/5828120
|View full text |Cite
|
Sign up to set email alerts
|

Mito‐TEMPO Alleviates Renal Fibrosis by Reducing Inflammation, Mitochondrial Dysfunction, and Endoplasmic Reticulum Stress

Abstract: Background Renal fibrosis is a common pathological symptom of chronic kidney disease (CKD). Many studies support that mitochondrial dysfunction and endoplasmic reticulum (ER) stress are implicated in the pathogenesis of CKD. In our study, we investigated the benefits and underlying mechanisms of Mito-TEMPO on renal fibrosis in 5/6 nephrectomy mice. Methods Mice were randomly divided into five groups as follows: control group, CKD group, CKD + Mito-TEMPO (1 mg·kg−1·day−1) group, CKD + Mito-TEMPO (3 mg·kg−1·day−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 43 publications
3
46
0
3
Order By: Relevance
“…Here we observed that mito-TEMPO decelerates IPF-LF senescence in vitro, and in pre-clinical studies for asthma and kidney disease, mitoTEMPO exhibits antifibrotic activity. 1,45,46 In this study, the expression of PGC-1α was increased in IPF-LFs 48 These splice variants are regulated differently to PGC-1α1 and evoke distinct biological programs. 49 In this study, we provide evidence that an auto-feedback loop exists between dysfunctional mitochondrial and senescence in LFs, involving increases in mitochondrial superoxide and mTORC1 activation.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Here we observed that mito-TEMPO decelerates IPF-LF senescence in vitro, and in pre-clinical studies for asthma and kidney disease, mitoTEMPO exhibits antifibrotic activity. 1,45,46 In this study, the expression of PGC-1α was increased in IPF-LFs 48 These splice variants are regulated differently to PGC-1α1 and evoke distinct biological programs. 49 In this study, we provide evidence that an auto-feedback loop exists between dysfunctional mitochondrial and senescence in LFs, involving increases in mitochondrial superoxide and mTORC1 activation.…”
Section: Discussionmentioning
confidence: 57%
“…In this regard, mitoTEMPO and other mitochondrial‐selective antioxidants such as MitoQ show potential as therapies for lung fibrosis. Here we observed that mitoTEMPO decelerates IPF‐LF senescence in vitro, and in pre‐clinical studies for asthma and kidney disease, mitoTEMPO exhibits anti‐fibrotic activity …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mito‐T is a potent mitochondria‐targeted antioxidant, which could act in ischemic tissues linked with hypoxia‐induced oxidative stress (Ding, Liu, Bi, & Zhang, 2017; Du et al, 2019; Du, Farhood, & Jaeschke, 2017; Li et al, 2018; Liu, Wang, Ding, & Wang, 2018; Nautiyal, Shaltout, Chappell, & Diz, 2019; Shetty, Kumar, & Bharati, 2019; Yang et al, 2018; Zhan et al, 2018). In the present study, mito‐T, a mitochondria‐targeted superoxide dismutase mimetic, dramatically reduced AMA‐induced mitochondrial oxidative stress, and thus effectively protected MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mito-T is a potent mitochondriatargeted antioxidant, which could act in ischemic tissues linked with hypoxia-induced oxidative stress (Ding, Liu, Bi, & Zhang, 2017;Du et al, 2019;Du, Farhood, & Jaeschke, 2017;Li et al, 2018;Liu, Wang, Ding, & Wang, 2018;Nautiyal, Shaltout, Chappell, & Diz, 2019;Shetty, Kumar, & Bharati, 2019;Yang et al, 2018;Zhan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The bladders of mice with SCI were manually voided twice a day until the mice were used for experimental purposes. A separate group of animals had osmotic pumps (Alzet 1007D; Alzet, Cupertino, CA) implanted subcutaneously to deliver MitoTempo (1 mg/kg/day in 0.9% saline; Cayman Chemical, Ann Arbor, MI) at the time of the injury until sacrifice. Three days after injury , animals were killed (CO 2 followed by exsanguination) and bladder tissue was collected for the assays described below.…”
Section: Methodsmentioning
confidence: 99%